2013
DOI: 10.1038/srep02246
|View full text |Cite
|
Sign up to set email alerts
|

The impact of p53 in predicting clinical outcome of breast cancer patients with visceral metastasis

Abstract: In the study, we analyzed role of p53 in predicting outcome in visceral metastasis breast cancer (VMBC) patients. 97 consecutive VMBC patients were studied. P53 positivity rate was 29.9%. In the p53-negative group, median disease free survival (DFS), and time from primary breast cancer diagnosis to death (OS1), time from metastases to death (OS2) were 25, 42.5, and 13.5 months, respectively. In the p53-positive group, they were 10, 22, and 8 months, respectively. Statistically significant differences in DFS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
50
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 32 publications
12
50
0
1
Order By: Relevance
“…Previous studies have shown that in human breast cancer samples, wild-type TP53 is associated with chemotherapeutic sensitivity (18). Other studies have reported that specific TP53 mutations or variants are associated with chemotherapeutic resistance (19)(20)(21). In addition, a role for TP53 in resistance to cisplatin treatment has been identified in ovarian cancer (22).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that in human breast cancer samples, wild-type TP53 is associated with chemotherapeutic sensitivity (18). Other studies have reported that specific TP53 mutations or variants are associated with chemotherapeutic resistance (19)(20)(21). In addition, a role for TP53 in resistance to cisplatin treatment has been identified in ovarian cancer (22).…”
Section: Discussionmentioning
confidence: 99%
“…A higher tumour grade, negative ER and PR status, and the more aggressive basal subtype were associated with abnormal p53 immunohistochemical expression or p53-positive status [70,72,73] . With regard to early breast cancers, some scientists have reported that a p53 mutation has no influence on the outcome and therefore, the value of p53 status is too weak to be recommended as a routine marker in clinical practice [74] .…”
Section: Markers Of Apoptosis and Cell Proliferation: Ki-67 Proliferamentioning
confidence: 99%
“…In addition, sequencing of the p53 gene in all breast cancers would be expensive and time-consuming for routine practice [70,71,73] . A higher tumour grade, negative ER and PR status, and the more aggressive basal subtype were associated with abnormal p53 immunohistochemical expression or p53-positive status [70,72,73] .…”
Section: Markers Of Apoptosis and Cell Proliferation: Ki-67 Proliferamentioning
confidence: 99%
“…This eventually results in the loss of P53's transcriptional activity towards downstream effector genes involved in anticancer signaling (2,13,19). Loss of P53 activity via mutations is associated with metastasis and poor prognosis in breast cancer (20,21), pancreatic cancer (2,22), astrocytoma and oligoastrocytoma (23), and stage 1 non-small cell lung carcinoma (24). Because mutant P53 (p53 MT ) can accelerate neoplastic progression, addressing the in situ mutational status of p53 may be indispensable for successful anti-cancer therapy (2,3,25,26).…”
Section: Introductionmentioning
confidence: 99%